Decoding the Cultural Significance of Pengaosan Tafsir Al-Ibriz in Kedawung, Mojo, Kediri: An Analysis of Social Meanings - Baydi, Ubaidillah; Laitsa Nailul Husna (UIN Sunan Kalijaga Yogyakarta, 2023)
This study investigates the impact of the tradition of Pengaosan Tafsir al-Ibriz on the socio-religious changes of the Kedawung community. The tradition is seen as a means of promoting social integration in the community, particularly in addressing multi-sectoral problems related to religious observance, cultural reception with religion, and economic cooperation. The research employs a qualitative approach, using observation, interviews, and documentation as data collection techniques, and is guided by the social construction phenomenology approach by Peter L. Berger and the structural functionalism theory by Talcott Parsons. The results show that the tradition of Pengaosan Tafsir al-Ibriz has become a participatory religious tradition that alternates between the residents' houses and has helped to awaken social and transcendental piety, creating a conducive environment and psychological calm. Furthermore, the tradition has strengthened the social integration of the residents by promoting empathy and affection, thereby boosting the economy through cooperation. This study highlights the significance of religious traditions in promoting social integration in communities facing multi-sectoral problems, and provides valuable insights for other communities seeking to promote social integration through religious traditions.